2018
DOI: 10.1371/journal.pone.0208160
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasmas are no exception to extracellular vesicles release: Revisiting old concepts

Abstract: Release of extracellular vesicles (EV) by Gram-negative and positive bacteria is being frequently reported. EV are nano-sized, membrane-derived, non-self-replicating, spherical structures shed into the extracellular environment that could play a role in bacteria-host interactions. Evidence of EV production in bacteria belonging to the class Mollicutes, which are wall-less, is mainly restricted to the genus Acholeplasma and is scanty for the Mycoplasma genus that comprises major human and animal pathogens. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 44 publications
(51 reference statements)
2
37
1
Order By: Relevance
“…Its ratio within the pellet samples was quite stable, whichever mycoplasma strain was studied, with a mean of 6.7 ϫ 10 Ϫ3 (n ϭ 15; minimum ϭ 4.5 ϫ 10 Ϫ3 ; maximum ϭ 8.5 ϫ 10 Ϫ3 ) and a supernatant/pellet fold change level which ranged from 0.04 to 0.7, an indication that FtsH was detected mostly in the cell pellet. This preliminary analysis confirmed that our procedure for sample preparation did not induce a noticeable level of release of membrane fragments in the supernatant attributable due to cell lysis or vesicle formation (21). In contrast, a number of proteases were highly expressed and detected both in the pellet and in the supernatant (0.5-fold to 2.5-fold change).…”
Section: Identification Of Genes Potentially Coding For Proteases In supporting
confidence: 75%
“…Its ratio within the pellet samples was quite stable, whichever mycoplasma strain was studied, with a mean of 6.7 ϫ 10 Ϫ3 (n ϭ 15; minimum ϭ 4.5 ϫ 10 Ϫ3 ; maximum ϭ 8.5 ϫ 10 Ϫ3 ) and a supernatant/pellet fold change level which ranged from 0.04 to 0.7, an indication that FtsH was detected mostly in the cell pellet. This preliminary analysis confirmed that our procedure for sample preparation did not induce a noticeable level of release of membrane fragments in the supernatant attributable due to cell lysis or vesicle formation (21). In contrast, a number of proteases were highly expressed and detected both in the pellet and in the supernatant (0.5-fold to 2.5-fold change).…”
Section: Identification Of Genes Potentially Coding For Proteases In supporting
confidence: 75%
“…EF-Tu is present within MVs derived from Gram-positive bacteria including Listeria monocytogenes (Coelho et al, 2019), Mycobacterium bovis , Mycobacterium smegmatis , Mycobacterium tuberculosis (Prados-Rosales et al, 2011), Staphylococcus aureus (Lee et al, 2009; Wang et al, 2018), Streptococcus agalactiae (Surve et al, 2016), Streptococcus pnuemoniae (Olaya-Abril et al, 2014), and Streptococcus pyogenes (Resch et al, 2016); Gram-negative bacteria including Acinetobacter baumannii (Kwon et al, 2009), Bacteroides fragilis (Zakharzhevskaya et al, 2017), Cronobacter sakazakii (Alzahrani et al, 2015), Escherichia coli (Lee et al, 2007), Francisella novicida (Pierson et al, 2011), Haemophilus influenzae (Sharpe et al, 2011), Klebsiella pneumoniae (Lee et al, 2012), Neisseria gonorrhoeae (Pérez-Cruz et al, 2015), Neisseria meningitidis (Vipond et al, 2006), and Pseudomonas aeruginosa (Choi et al, 2011); and in six Mycoplasma species (Gaurivaud et al, 2018). Indeed, EF-Tu was reported as one of the most abundant protein in some of these studies (Lee et al, 2009; Pérez-Cruz et al, 2015; Gaurivaud et al, 2018). Interestingly, several MVs that contain EF-Tu have been reported to increase virulence (Surve et al, 2016), modulate immune responses (Prados-Rosales et al, 2011; Sharpe et al, 2011; Alzahrani et al, 2015), and offer protection to infection via immunization (Vipond et al, 2006; Pierson et al, 2011; Olaya-Abril et al, 2014).…”
Section: Moonlighting Proteins In Bacteriamentioning
confidence: 99%
“…and even physiological or pathological environment of donor cells or tissues including hypoxia, hyperthermia, infections, circadian rhythms, hormones, and stage of cell cycle, etc. (Burger et al, 2017 ; Németh et al, 2017 ; Gaurivaud et al, 2018 ; Ludwig et al, 2019 ; Pegtel and Gould, 2019 ; Kalluri and LeBleu, 2020 ; Zubair et al, 2020 ). Moreover, the existing isolation and purification technologies (e.g., ultracentrifugation, nanoscale flow cytometry, immunoprecipitation/affinity capture, Exosome Isolation Reagent, etc.)…”
Section: Discussionmentioning
confidence: 99%